Carbon resource richness shapes bacterial competitive interactions by alleviating growth‐antibiosis trade‐off. (11th February 2019) - Yang, Chunlan; Dong, Yue; Friman, Ville‐Petri; Jousset, Alexandre; Wei, Zhong; Xu, Yangchun; Shen, Qirong
Abstract: Antibiosis and resource competition are major drivers shaping the assembly, diversity and functioning of microbial communities. While it is recognized that competition is sensitive to environmental conditions, it is unclear to what extent this mediated by the availability of different carbon resources. Here, we used a model laboratory system to directly test this by exploring how carbon resource richness and identity shape resource competition and antibiosis between plant probiotic Bacillus amyloliquefaciens and phytopathogenic Ralstonia solanacearum bacteria. We found that while sugars typically promoted B. amyloliquefaciens growth, organic and amino acids increased the production of both bacillaene and macrolactin antibiotics and the direct inhibition of R. solanacearum . In contrast, when multiple different carbon resources were available, B. amyloliquefaciens could efficiently grow and produce antibiotics at the same time. Together, these results suggest that high carbon resource richness allows concurrent expression of growth‐ and antibiosis‐related traits, potentially altering bacterial competitive dynamics and plant growth promotion in microbial communities. Aplain language summary is available for this article. Abstract : Plain Language Summary